Nitrogen isotopic baselines and implications for estimating foraging habitat and trophic position of yellowfin tuna in the Indian and Pacific Oceans. (March 2015) - Lorrain, Anne; Graham, Brittany S.; Popp, Brian N.; Allain, Valérie; Olson, Robert J.; Hunt, Brian P.V.; Potier, Michel; Fry, Brian; Galván-Magaña, Felipe; Menkes, Christophe E.R.; Kaehler, Sven; Ménard, Frédéric
Abstract: Assessment of isotopic compositions at the base of food webs is a prerequisite for using stable isotope analysis to assess foraging locations and trophic positions of marine organisms. Our study represents a unique application of stable-isotope analyses across multiple trophic levels (primary producer, primary consumer and tertiary consumer) and over a large spatial scale in two pelagic marine ecosystems. We found that δ 15 N values of particulate organic matter (POM), barnacles and phenylalanine from the muscle tissue of yellowfin tuna all showed similar spatial patterns. This consistency suggests that isotopic analysis of any of these can provide a reasonable proxy for isotopic variability at the base of the food web. Secondly, variations in the δ 15 N values of yellowfin tuna bulk-muscle tissues paralleled the spatial trends observed in all of these isotopic baseline proxies. Variation in isotopic composition at the base of the food web, rather than differences in tuna diet, explained the 11‰ variability observed in the bulk-tissue δ 15 N values of yellowfin tuna. Evaluating the trophic position of yellowfin tuna using amino-acid isotopic compositions across the western Indian and equatorial Pacific Oceans strongly suggests these tuna occupy similar trophic positions, albeit absolute trophic positions estimated by this method were lower than expected. This study reinforces the importance of considering isotopic baseline variability for diet studies, and provides new insights into methods that can be applied to generate nitrogen isoscapes for worldwide comparisons of top predators in marine ecosystems.